2017
DOI: 10.1017/s1368980016003645
|View full text |Cite
|
Sign up to set email alerts
|

Regular breakfast consumption is associated with higher blood vitamin status in adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study

Abstract: Objective: The present study aimed to examine the association between different breakfast consumption patterns and vitamin intakes and blood vitamin concentrations in European adolescents. Design: Breakfast consumption was assessed by a questionnaire. Vitamin intake was calculated from two 24 h recalls. Blood vitamin and total homocysteine (tHcy) concentrations were analysed from fasting blood samples. Setting: The European Commission-funded HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
0
25
0
8
Order By: Relevance
“…From the 33 included articles, only 3 articles (9.1%) were longitudinal versus 90.9% of the studies ( n = 30), which were cross-sectional. From the 33 included studies, 17 were performed in representative samples of the correspondent population [ 16 , 28 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Table 3 shows details of the articles, which included the impact of breakfast consumption on micronutrients intake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 33 included articles, only 3 articles (9.1%) were longitudinal versus 90.9% of the studies ( n = 30), which were cross-sectional. From the 33 included studies, 17 were performed in representative samples of the correspondent population [ 16 , 28 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Table 3 shows details of the articles, which included the impact of breakfast consumption on micronutrients intake.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous authors observed that children with obesity were more likely to skip breakfast [ 9 , 10 , 11 ], and these children had a high risk of chronic diseases as type 2 diabetes [ 12 , 13 , 14 ], dyslipidemia or cardiovascular diseases [ 7 , 8 , 15 ]. Likewise, previous authors observed that some vitamin deficiencies could be associated with fatness and other diseases, [ 16 , 17 , 18 ] and can be considered a critical public health issue [ 19 , 20 ]. Some studies also observed that in both children and adolescents, breakfast consumption has a positive effect on cognitive performance [ 21 ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…W 2017 r. ponownie wykazano korzyści ze spożywania śniadań. W badaniu: " HELENA Study" udowodniono, że regularne spożywanie śniadania przekładało się na wyższą koncentrację stężenia witamin we krwi [12]. Natomiast pomijanie posiłku porannego było związane z osłabieniem zdolności intelektualnych [6].…”
Section: Wyniki I Ich Omówienieunclassified
“…Analiza częstości spożycia produktów mięsnych w świetle zebranych danych jest trudna, ponieważ analizowano tylko posiłki konsumowane podczas choroby układu sercowo -naczyniowego czy choroby autoimmunologiczne, występujące wraz ze wzrastającym przeżywieniem znacznej części europejskiej populacji i przejmowaniem zachodniego stylu żywienia. W świetle dotychczasowej wiedzy, autorzy uznali za konieczne wprowadzenie edukacji żywieniowej mającej na celu zapoznanie studentów z zaleceniami zdrowej diety propagowanej przez liczne towarzystwa żywieniowe [1,2,7,12,14].…”
Section: 4%unclassified